Bilik Toleransi Sebagai Simbol Gerakan Sosial Keagamaan Masyarakat Desa Segaran Wates Kediri - Putera, Faga Pandunata; Harianto, Budi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Segaran Village is one of the villages in Wates District, Kediri Regency. The community of Segaran Village is a heterogeneous society, especially in terms of religion, namely Christianity and Islam. With Islam being a minority in Segaran Village, it does not make them feel marginalized or conversely, Christians feel powerful. The existence of a tolerance booth is an example of the high level of tolerance in Segaran Village. The main purpose of establishing this tolerance booth is a place for communication. Therefore, this research aims to find out how the tolerance booth a is a symbol of the social religious movement of the people of Segaran Village and how the social interactions of the people in Segaran Village. This type of reseacrh is qualitative research wit a case study approach. The data collection techniques used in research were interviews and observation. This research uses Georg Simmel’s theory of social interaction which focues on the concept of interaction based on type and form. The results of the research show that the tolerance booth as a symbol of the social reilgious movement of the peopleof Segaran Village, has become its own symbol of heterogeneous society, especially in terms of religion and the people of Segaran Village who highly value tolerance.